The Poem for the Opening of the Picador Café: History – Myth – Literature - Maleszyńska, Joanna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The founders of the first literary café in reborn Poland, namely ‘Pikador’ in Warsaw, chose a poem by Jan Lechoń for the inauguration ceremony in November 1918. In the poem, titled Mochnacki, the young poet recollects a historical concert of Maurycy Mochnacki, a Romantic tribune of the 19th-century Warsaw, a pianist and a writer. Different possibilities of interpretation of the work, which is heavily emotional – ranging from patriotic poetry, through an almost social satire to an intimate confession encoded in the form of a description of a piano concert and reactions of the foreign audience to it – are not contradictory as they complement each other well.